EFFECTS OF PLATELET-RICH PLASMA INJECTIONS ON OSTEOARTHRITIC PATIENTS - PRAKASH, D. RAVI; KUMAR, C. SIVA; NARAYANA, SATYA; DEEPAK (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: Various treatment options are available for knee osteoarthritis such as medical treatment with NSAID, conservative management with platelet-rich plasma (PRP) and corticosteroids. We have done this prospective study to know the use and safety of platelet- rich plasma (PRP) injections in knee osteoarthritis (KOA) patients. We know platelet rich plasma (PRP) clinical and functional outcome in knee osteoarthritis (KOA) by doing this study and using the available literature. Methods: This prospective study consisted of a total number of 96 patients suffering from knee osteoarthritis. Both males and females are included. Intra-articular injection of platelet rich plasma (PRP) was given in sterile conditions and clinical and functional outcomes were analyzed with Western Ontario and McMaster University Arthritis Index (WOMAC), Visual Analogic Scale (VAS), and Knee Society score (KSS). This study is done in a tertiary care institute during the study period. Results: Most patients were females aged>40 years with knee osteoarthritis. The injections of platelet rich plasma (PRP) showed results at three, six and twelve months follow-up showed significantly reduced WOMAC scores, Visual Analogic Scale (VAS) and Knee Society score (KSS). No complications were observed during the follow-up period. Conclusion: The results confirm the efficacy of the PRP injections on Knee osteoarthritis, suggesting that decreasing pain was obtained one month after injection, with the best results observed after 12 months—however, a more extensive study group. Follow-up is required for a prolonged period to assess the efficacy of PRP injection.